Efficacy of the Canalith Repositioning Procedure in Benign Paroxysmal - Karim, Abul Mansur Md Rezaul; Hasanuzzaman, Md; Chowdhury, Mohammed Abu Yusuf; Tayeb, Md Abu (Medicine Today, 2016)
Benign paroxysmal positional vertigo (BPPV) is paroxysms of vertigo occurring with certain head movements, typically looking up or turning over in bed comprising about 20% of Dizziness cases. This study was carried out to evaluate the Efficacy of canalith repositioning procedure(CRP) in BPPV. A randomized clinical trial including 80 patients with BPPV was performed Medicine & Neurology Outpatient Department, Chittagong Medical College Hospital. The patients were randomly divided into two groups. Group A treated by anti-vertigo drug and CRP, Group B treated by anti-vertigo drug alone. All patients were followed up in hospital at one week after & 4 weeks. The rates of effectiveness of CRP treatment and the control treatment for were 86.8% and 59.4%, respectively. There was a significant difference (27.4%) in the outcomes of the CRP & control groups (P <.05). Mean total drug use for the group A was 10 ± 1, whereas it was 30 ± 1.5 for group B, mean difference = 20 (P < .001, highly Significant). At 4 Weeks, subjective improvement and symptom free occurred in 94.7% patients in group A and 73% patients in group B (difference21.7%). Complications in the CRP group were observed in 10.6% of the patients. This study demonstrated that canalith repositioning procedure (CRP) was effective in the treatment for benign paroxysmal positional vertigo insofar as it provided faster recovery & low drug dependence. Complications of CRP were limited to 10.6% of patients. Medicine Today 2015 Vol.27(2): 23-27